Neocryptolepine: A Promising Indoloisoquinoline Alkaloid with Interesting Biological Activity. Evaluation of the Drug and its Most Relevant Analogs - Larghi, Enrique Leandro (2015)
Plants are one of the most important resources for the discovery of new drugs. The potential of natural compounds as new drug leads is clearly illustrated by the discovery and development of many modern medicines. This is an encouraging factor that drives natural products research in the vegetable kingdom. Neocryptolepine is a tetracyclic nitrogen heterocycle isolated from the African climber Cryptolepis sanguinolenta, which is widely used in traditional African medicine in many countries of Central and West Africa. The natural product is one of the representative examples of the small family of indolo[2,3-b]quinoline alkaloids, being endowed of multiple biological activities, including DNA-binding and inhibition of the enzyme topoisomerase II. It is also cytotoxic, antibacterial, antifungal and molluscicidal, also displaying antiprotozoal activity, particularly as antitrypanosomal, antileishmanial, antischistosomal and antiplasmodial. Some of these activities have been related to the product’s ability to bind to DNA and to inhibit topoisomerase II; however, the exact mechanisms behind all of the observed bioactivities have not been comprehensively clarified. Major research activities regarding neocryptolepine have been focused into two seemingly opposite fields, related to its cytotoxic and antimalarial properties. Optimization of the natural product as a cytotoxic agent implied improvements in its bioavailability and activity, while the need of non-cytotoxic compounds guided the design and optimization of antimalarial agents. Therefore, the aim of the present article is to systematically review the current knowledge about the diversity of the biological activities related to neocryptolepine, its analogs and derivatives.